CHIZMA GEOMETRIYA VA MUHANDISLIK GRAFIKASI FANIDA POZITSION VA METRIK MASALALARNI ISHLASH (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
In this article, it is proposed to make  solving metric and positional task which are studied in engineering graphics, in other words, on the basis of theoretical knowledge by hand, and then in practice through the computer programs.  Theoretical knowledge teaches to read drawings, to imagine spatially by the help of given drawings and what actions need to be taken to solve a problem, as well as the laws and rules.